Bone marrow‐derived progenitor cells in de novo liver regeneration in liver transplant. Issue 9 (23rd April 2015) - Lee, Sung‐Gyu; Moon, Sung‐Hwan; Kim, Hee‐Je; Lee, Ji Yoon; Park, Soon‐Jung; Chung, Hyung‐Min; Ha, Tae‐Yong; Song, Gi‐Won; Jung, Dong‐Hwan; Park, Hojong; Kwon, Tae‐Won; Cho, Yong‐Pil
<x xml:space="preserve">Abstract</x> The study was designed (1) to examine the hypothesis that circulating progenitor cells play a role in the process of de novo regeneration in human liver transplants and that these cells arise from a cell population originating in, or associated with, the bone marrow and (2) to investigate whether the transplanted liver volume has an effect on the circulating recipient‐derived progenitor cells that generate hepatocytes during this process. Clinical data and liver tissue characteristics were analyzed in male individuals who underwent sex‐mismatched adult‐to‐adult living donor liver transplantation using dual left lobe grafts. Dual left lobe grafts were examined at the time of transplantation and 19 to 27 days after transplantation. All recipients showed recovery of normal liver function and a significant increase in the volume of the engrafted left lobes after transplantation. Double staining for a Y‐chromosome probe and the CD31 antigen showed the presence of hybrid vessels composed of recipient‐derived cells and donor cells within the transplanted liver tissues. Furthermore, CD34‐expressing cells were observed commingling with Y‐chromosome+ cells. The ratio of recipient‐derived vessels and the number of Y+CD34+ cells tended to be higher when smaller graft volumes underwent transplantation. These findings suggest that the recruitment of circulating bone marrow–derived progenitor cells could contribute to vessel formation and de novo regeneration in human liver transplants. Moreover, graft volume may be an important determinant for the active mobilization of circulating recipient‐derived progenitor cells and their contribution to liver regeneration. Liver Transpl 21:1186–1194, 2015. © 2015 AASLD.